Clinical study to evaluate the efficacy of Platelet rich Fibrin in Reconstruction of the interdental Papilla - يوسف, تهامة; اسماعيل , أحمد (Latakia University Journal -Medical Sciences Series, 2022)
loss of Interdental papilla is a characteristic clinical finding in the field of ​​periodontal diseases, usually associated with aesthetic concerns, and functional problems. Many treatment options are available to manage gingival recession and include surgical and nonsurgical techniques. Most treatments are conservative and aim to access a long-term aesthetic result. This study was carried out to evaluate efficacy of Platelet rich Fibrin in Reconstruction of the interdental Papilla. The sample included ( 20) sites of loss of Interdental papilla cases found in(8) patients Of the Department of periodontology , Faculty of Dentistry, Tishreen University. Each patient had undergone an initial periodontal treatment, including oral hygiene instructions, plaque control, and scaling and root planing, followed by re-evaluation. All clinical recordings of this research; distance from contact point to tip of interdental Papilla were performed immediately before surgery (baseline) and after 3- 6 months interval following periodontal surgery.The gap between contact point and tip of interdental papilla has been reduced to 57% after first month and 91 after 6 months. Conclusion The use of PRF is an effective therapeutic option for Reconstruction of the interdental Papilla, although it is still too early to predict the long-term consequences associated with it.